3D Conductive Network Supported Monolithic Molybdenum Disulfide Nanosheets for High‐Performance Lithium Storage Applications. Issue 7 (8th March 2017) - Liu, Mingkai; Liu, Yuqing; Tang, Buzheng; Zhang, Peng; Yan, Yan; Liu, Tianxi
Abstract : Hierarchical 3D graphene nanoribbons/carbon nanotubes–molybdenum disulfide (GR/CNT‐MoS2 ) nanocomposites have been facilely and controllably prepared. The GR/CNT matrix, which is prepared by partial unzipping of multiwalled CNTs, possesses good conductive networks by bridging graphene nanoribbons on different CNTs. MoS2 with monolithic morphologies is anchored on the GR/CNT conductive networks, achieving the formation of hierarchical GR/CNT‐MoS2 nanocomposites. As a result of the good dispersion of MoS2, a large specific surface area (238 m 2 g −1 ) of GR/CNT‐MoS2 nanocomposite has been achieved. Excellent electrochemical performance including high specific capacity (1245 mA h g −1 ) and good cycling stability (90.9% capacity retention after 200 cycles) of the GR/CNT‐MoS2 nanocomposites is achieved due to the full exposure of the active sites of MoS2 nanoflakes, and high electron transport ability of the GR/CNT substrate. These novel GR/CNT‐MoS2 nanocomposites show promising application in lithium ion batteries, and further provide a new way to design and develop new anode materials. Abstract : Hierarchical 3D graphene nanoribbons/carbon nanotubes–molybdenum disulfide (GR/CNT‐MoS2 ) nanocomposites with unique structures are designed by tightly anchoring monolithic MoS2 nanoflakes on the surface of conductive GR/CNT network, which exhibit promising electrochemical performance of high capacity (1245 mA h g −1 ), good rate performance, and excellent cycling stability (90.9% capacity retention after 200 cycles).